Conservation Research, Policy and Practice - Sutherland, William J.; Brotherton, Peter N. M.; Davies, Zoe G.; Ockendon, Nancy; Pettorelli, Nathalie; Vickery, Juliet A. (Life Sciences, 2020)
Developed following the success of an international symposium, this book examines how to make conservation more effective through strengthening links between science research, policy and practice. Ideal for practitioners, researchers, graduate students and policymakers. This title is also available as Open Access on Cambridge Core.